Effects of anti-drug antibody on clinical efficacy and adverse reactions of immunotherapy for non-small cell lung cancer - ZHAO Xianlan; LI Jixi; YANG Qiao; LI Shixun; YU Yongxin; LI Feng; LI Mengxia; SUN Jianguo (Di-san junyi daxue xuebao, 2021)
Objective To explore the effects of anti-drug antibody (ADA) on clinical efficacy and adverse reactions in patients with non-small cell lung cancer (NSCLC) treated with immune checkpoint inhibitors (ICIs). Methods A total of 26 patients with stage Ⅲ/Ⅳ NSCLC undergoing pembrolizumab or nivolumab treatment from April 2016 to September 2019 were collected from the Second Affiliated Hospital and Daping Hospital of Army Medical University. Blood samples were collected about 2 months after the first infusion of ICIs. The level of ADA in plasma were measured by enzyme-linked immunosorbent assay. The effects of ADA on the clinical efficacy, disease progression and immune-related adverse events (irAEs) of ICIs were analyzed. Results In 12 patients treated with nivolumab, the results of ADA test were negative, the best overall response rate (bOR) was 25.0%, the median progression-free survival (mPFS) was 4.1(1.9~26.9) months, and the median overall survival (mOS) was 12.4 (4.8~26.9) months. In 14 patients treated with pembrolizumab, bOR was 50.0%, mPFS was 10.9 (2.2~25.3) months, and mOS was 19.0 (5.2~29.6) months; 3 of 14 patients were ADA-positive, 11 were ADA-negative. mPFS (9.9 vs 12.4 months, P=0.280), mOS (19.0 vs 29.6 months, P=0.874) and median time to radiographic progression after blood sampling (7.5 vs 8.6 months, P=0.365) were significantly shorter in the ADA-positive patients than the ADA-negative patients. irAEs occurred in 2 (66.7%) ADA positive patients and 3 (27.3%) ADA negative patients. Conclusion ADA monitoring in NSCLC patients has certain clinical value for the treatment of ICIs, and ADA positive of pembrolizumab has an effect on the shorter survival time of patients. However, the effect of ADA status is not significant on bOR and irAEs.